Pertanggung Jawaban Korporasi Dan Pengurus Terhadap Kecelakaan Kerja Yang Menyebabkan Tenaga Kerja Meninggal Dunia Studi Kasus Pada Sub Kontraktor Pt Pertamina Hulu Rokan - Chindy Maria Rohani Sipahutar; Firdaus Firdaus; Davit Rahmadan (Universitas Malayati, 2025)
Employment is everything related to workers before, during and after the work period. It cannot be denied that the role of labor in national development is increasing accompanied by the various challenges and risks it faces so that in turn it will be able to increase national productivity. One of the efforts to protect workers is to carry out supervision regarding the implementation of employment. This is because employment development in Indonesia is part of national development based on Pancasila and the 1945 Constitution, which is carried out in the context of community development to increase the dignity and self-respect of workers as well as realizing welfare, justice and equitable prosperity, both materially and spiritually.This research is classified as research with an empirical juridical approach. Empirical juridical research is legal research regarding the application or implementation of normative legal provisions directly to each specific legal event that occurs in society.Based on the results of the research and discussion, it can be concluded. First: implementation of corporate responsibility for work accidents that cause workers to die at the subcontractor PT Pertamina Hulu Rokan reflect the existence of weaknesses in law enforcement related to Occupational Health and Safety, which involves three the main elements are legal substance, legal structure, and legal culture. Second: the criminal liability of corporations and their management for work accidents that cause workers to die at PT Pertamina Hulu Rokan has given great attention to the issue of criminal liability of corporations and their management. In this sentence, criminal punishment was only given to the company management, namely the defendant Harry Rahmady, who was sentenced to 3 (three) months in prison. Even though the sentence handed down to Harry Rahmady was inadequate and did not provide proper justice for the victim and his family. It is felt that a prison sentence of 3 (three) months is not commensurate with the severity of the consequences of the accident that occurred. In addition, the relatively light sentence for company management does not touch the responsibility of the corporation itself